An Environment-Friendly Rock Excavation Method - Ze Gan; Xi Yang; Yunpeng Zhang; Xu Wu; Jie Wang (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Blasting is used as an economical tool for rock excavation in mines. However, part of the explosive energy is converted into elastic waves, resulting in ground vibration and excessive vibration, which may cause damage to nearby buildings. Meanwhile, toxic gases are also produced during the explosion. In this paper, an environment-friendly method for rock excavation is proposed. A series of vibration tests were conducted, and the peak particle velocity was monitored. The results showed that the proposed method can replace the conventional blasting method in mines. Besides that, the vibration caused by the proposed method is much smaller than by the conventional method. By adjusting the direction of the high-pressure gas injection, buildings around the mine can be protected well from vibration. Also, the production of toxic gases during excavation will no longer be a problem. Thus, a milder environmental impact can be achieved. However, the rocks excavated by the proposed method are relatively large, which still need to be broken further. On this issue, further study is required.